Diversity Of Plant Types In Forest Areas Of Other Use Areas In Pantan Cuaca Subdistrict, Gayo Lues District - Handayani, Triaty; Anhar, Ashabul; Ganafi, Ahmad; Ridwan (JURNAL AGRIMENT, 2024)
Forest is an expanse of land dominated by plants. The high diversity of plants shows how many different types of plants are found in an area and is a source of life for living creatures in and around forest areas. This research aims to determine the composition of plant species in the Other Use Area (OUA) forest area in the Weather Pantan District, Atu Kapur, Seneren and Kuning Kurnia Villages. This research method takes samples using a systematic random system. The sample instensity of 0.12% with 25 sample plots. The results of the research showed that 19 plant species from 12 families were found with a total of 520 individuals at the sapling, pole and tree level. These plants are dominated by the Jamu Wood (Syzygium grande) and Geseng Bunge (Lithocarpus sp.) types with a total of 94 individuals. The species diversity index at all levels (saplings, poles and trees) is in the medium category and the distribution is stable based on the species evenness index at each growth level.